The Relevance of Deviation in the Study of Poetry: A Critical Analysis - Onu, Mercy Agha (EBSU Journal of Social Sciences and Humanities, 2021)
Deviation is the violation of the rules or norms. In other words, deviation is the tool that is used by the poet to deviate from norm and conventions. There are nine different kinds of deviation found in poetry. The objective of this paper is to look into deviation as a very effective stylistic device in poetry. It studies the manipulation of language in different poetry for the creation of aesthetic value. This paper, therefore, examines deviation in poetry and it is discovered that all these levels of deviation are essential for readers to understand the text and to create emotion. The study finds that deviation helps to increase Igbo vocabularies and some are pleasurable sound. It helps to know the different dialects in Igbo language.